TOWARDS PRINCIPLED FISHERIES GOVERNANCE AUSTRALIAN AND INDONESIAN : APPROACHES AND CHALLENGES - Chomariyah, Chomariyah (UI Scholars Hub, 2014)
The principled fisheries governance coexist two concepts under the precautionary principle. The first one, based on the strengthening of the concept of environmental protection, aims to promote a prevention proportional to the potential risks. The second one looks for the eradication of risks and it may even require the ‘‘proof demand’’ of innocuousness. Implementation of the precautionary principle in the fishing sector became established as a reaction in general situation of world fish stocks to guarantee the sustainability of the exploitations. This paper tries to stress the implementation of the precautionary principle in Australia’s practice to application in Indonesia’ legal framework of fisheries. The Concept of precautionary principle must analysis with compatibility principle before implementation in national level. Needed to fisheries governance of the management and conservation of legislation or establish a new national single instrument of conservation of fisheries. There should be more research on precautionary principle in fisheries conservation especially on its complexity of legal instrument. Currently, the implementation of precautionary principle must be done in Indonesia. Thus, it evaluates the concepts applied in Indonesia fisheries management and conservation, and it concludes by pointing out solution of the problems derived from its implementation.